Community voices on Climate and Security: Summary results for Senegal - Medina, Leonardo; Sarzana, Carolina; Krendelsberger, Alexandra; Madurga Lopez, Ignacio M.; Villa, Victor; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR System Organization, 2022)
"This report summarizes preliminary results from fieldwork research conducted in Senegal during November, 2022. It is meant to expand our comprehension of climate-related security risks in Senegal, by examining the way local communities capitalise on everyday experience to develop a shared understanding around the effects of climate change over their livelihoods and wellbeing, along with the insecurity problems they collectively face. Ongoing community-level responses are also discussed, identifying short-term coping and long-term adaptive strategies which have most successfully enhanced local capacities towards managing climate risks, along with those which are currently being overwhelmed. This evidence on adaptive strategies is then used as a base to propose solutions based on collective action, through a reflective dialogue with community members, meant to address climate-related security risks and to challenge institutional structures that sustain the underlying causes of vulnerability."